Development of Calcium Carbonate-based Nano- and Micro- Structural Materials - DONNELLY, FEARGHAL COLM (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2020)
Calcium carbonate is a ubiquitous material, which has a high commercial importance and a variety of important applications. The main goal of this work is the development of new CaCO3 based nano- and micro-structural materials using various synthetic techniques. Here, we present our work on precipitation-based syntheses, a novel dry ice carbonation method and CO2 bubbling for the preparation of nano- and micro-particles of CaCO3. Precipitation reactions were used to finely control the synthesis of unique CaCO3 materials, and subsequently their chiral and luminescent properties. A unique dry ice carbonation method was developed enabling us to produce CaCO3 morphologies which are not typically attainable using standard preparation approaches and we have subsequently doped them with trivalent lanthanides resulting in CaCO3 bow ties presenting red and green phosphorescence. Finally, CO2 bubbling, which is the preferred method for industrial carbonation, was studied and the parameters affecting its synthesis were subsequently refined. We believe that this work will contribute to further development of CaCO3 based materials with a range of potential applications.
APPROVED
Keywords: Nanomaterials; Calcium carbonate; Chirality; Luminescence